Risk Factors for Central and Lateral Lymph Node Metastases in Patients With Papillary Thyroid Micro-Carcinoma: Retrospective Analysis on 484 Cases - Huang, Yijie; Yin, Ying; Zhou, Wenyi (Frontiers in Endocrinology, 2021)
Background: Papillary thyroid micro-carcinoma (PTMC) is deﬁned as a tumor with a larger diameter ≤1cm which has an indolent course and satisfying prognosis. However, the incidence of lymph node metastasis of PTMC cannot be ignored. The aim of this study was to assess the incidence of lymph node metastasis in PTMC patients, as well as to evaluate the risk factors for both central lymph node metastases (CLNM) and lateral lymph node metastases (LLNM). Methods: Patients who underwent thyroidectomy from January 2017 to October 2020, and pathologically diagnosed with PTMC were enrolled in our study and their medical records were collected and analyzed. Results: A total of 484 PTMC patients were included. The incidence of central and lateral lymph node metastasis was 49.6% and 9.1%, respectively. Multivariate analysis demonstrated as independent risk factors for CLNM male sex, age <40 years, largest tumor size ≥5mm and bilaterality. Extrathyroidal extension, presence of CLNM, number of CLNM ≥5 were strong indicators for LLNM. Conclusion: The incidence of lymph node metastases in PTMC is non-negligible. The identification of potential risk factors for CLNM and LLNM would help tailor individual surgical interventions for patients with PTMC.